2020
DOI: 10.3389/fpsyg.2020.01734
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Children’s Media Use and Language and Literacy Skills

Abstract: Media use is a pervasive aspect of children's home experiences but is often not considered in studies of the home learning environment. Media use could be detrimental to children's language and literacy skills because it may displace other literacyenhancing activities like shared reading and decrease the quantity and quality of caregiver-child interaction. Thus, the current study asked whether media use is associated with gains in children's language and literacy skills both at a single time point and across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
0
17
0
1
Order By: Relevance
“…Indeed, previous studies also suggested that parental characteristics and home environment (e.g., socioeconomic status and parental support) mattered more and were stronger predictors of children’s neurodevelopment than the amount of screen media use per se 10 , 30 , 31 . Another possible explanation for the inverted U-shape relationship could be that children watching moderate amount of TV watch programs of higher quality, and this may be beneficial for their language compared to non-watchers 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies also suggested that parental characteristics and home environment (e.g., socioeconomic status and parental support) mattered more and were stronger predictors of children’s neurodevelopment than the amount of screen media use per se 10 , 30 , 31 . Another possible explanation for the inverted U-shape relationship could be that children watching moderate amount of TV watch programs of higher quality, and this may be beneficial for their language compared to non-watchers 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Segers and Kleemans ( 2020 ) only found relations between analog (but not digital activities at home such as reading to the child or playing language and word games) with children’s language skills. The authors argued that one reason of the absence of relations between digital HLE and child language skills might lay in the quality of digital HLE (Segers & Kleemans, 2020 ; see Dore et al, 2020 , for similar findings on relations between media use and language skills and interpretation of results). Notably, in their study, there was a relatively high number of missing answers on questions on digital activities at home.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the historic context when the ECCE study took place (such technology being much less common in 2010 when the first children were recruited to the evaluation). Although ECCE investigated television viewing alongside the HLE (as a kind of 'displacement activity'; Dore, et al, 2020), future research could also explore the extent to which smart phone and/or tablet use is related to other kinds of home learning activities for this very young age group. This would also help to inform the currently sparse and at-times contradictory evidence concerning how these devices (and apps on them) can benefit and/or hinder child development (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…During the development of the THLE, two items were devised that focused not on the THLE (on activities concerning adulttoddler interaction) but instead on toddler television watching as a kind of 'displacement activity' (e.g. Dore et al, 2020) from the interactions that promote learning. These two items were developed alongside the THLE items in order to equip the ECCE study with the ability to describe other things that toddlers may have been doing other than engaging in interactions linked to learning and development.…”
Section: Methodsmentioning
confidence: 99%